HPV vaccination improves immune response in children with respiratory papillomatosis - Miguel A. Prieto-Islas; Esmeralda Godoy-Dahbura; Diana C. Villalpando-Sánchez; Cristina Cortés-Benavides; Eduardo Hernández-Cuellar; Denisse Castro-Eguiluz; Hiram Alvarez-Neri; Oscar Medina-Contreras (Scientific Reports)
Abstract Recurrent respiratory papillomatosis (RRP) is a pathology characterized by the presence of neoplasm in the epithelium of the airways, where the larynx is the main affected organ. The cause of this disease is the low-risk Human Papillomavirus (HPV), where subtypes 6 and 11 are the most frequent. The only proven effective treatment is surgical resection of the lesions, and although there are adjunctive treatments to try to reduce the recurrence of neoplasms, it has not been proven that there is an effective alternative that achieves this effect. A proposal as adjuvant therapy is the HPV vaccine; although used in adults to treat the disease, the effect it has on immunological changes in a pediatric population with PRR has not been studied, so the objective of this work is to assess the efficacy of vaccination as an adjuvant treatment, by observing the immunological changes that are generated after vaccination, measuring the antibody titer as well as the cytokine profile present in the patients and relating it to the impact at the clinical in pediatric population. For this, blood samples and biopsies obtained by laryngeal surgery from 10 patients before and 6 months after completing the HPV vaccination scheme were compared. Viral load of the HPV6/11 serotypes was measured by qPCR, observing a decrease in copy number of both subtypes after vaccination. The antibody titer in the serum of the same patients was measured by ELISA, observing an increase in the amount of IgG antibodies without finding modifications in the IgM antibodies against HPV L1 protein. In addition, HPV vaccination was associated with a decrease in the immunosuppressive cytokine IL-10 in papilloma tissue and a significant increase in the pro-inflammatory cytokine TNFα in serum, suggesting a shift towards a Th1-mediated immune response. All these changes had an impact on the number of surgeries that were performed to remove the neoplasms, where there was a decrease in these during a six-month follow-up after vaccination. In conclusion, the vaccination as adjuvant therapy increased the number of IgG antibodies against the virus. It increased the amount of pro-inflammatory cytokines at the systemic level, reducing the viral load and the number of recurrences of papillomas.